(untitled) (Research, Society and Development, 2025)
The present study aimed to evaluate the deleterious effects of the use of local anesthetic associated with vasoconstrictors (Lidocaine + epinephrine 1:200000) in the extremities, for which it was administered to the middle portion of the tail of Wistar rats. Twenty healthy male rats weighing approximately 250g were used. These animals were divided into four groups containing five rats each. The tail of animals from groups G1, G2 and G3 was anesthetized subcutaneously with lidocaine at a dose of 2mg/kg, 4mg/kg, 7mg/kg, respectively, all associated with epinephrine 1:200.000. Subjective (appearance, color, edema) and objective (tail diameter) data were collected. Subsequently, histopathological analysis of the tissue inoculated with the drug was performed in search of signs of necrosis. After analyzing the data collected, there were no significant signs of necrosis, so it was possible to infer that the use of lidocaine associated with epinephrine (1:200000) in body parts whose vascularization is of small caliber, such as the tail of Wistar rats, would be safe.